2011
DOI: 10.1007/s00726-011-1023-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ornithine decarboxylase decreases ventricular systolic function during induction of cardiac hypertrophy

Abstract: Ornithine decarboxylase (ODC), the first enzyme of polyamine metabolism, is rapidly upregulated in response to agents that induce a pathological cardiac hypertrophy. Transgenic mice overexpressing ODC in the heart (MHC-ODC mice) experience a much more dramatic left ventricular hypertrophy in response to β-adrenergic stimulation with isoproterenol (ISO) compared to non-transgenic controls. ISO also induced arginase activity in transgenic hearts but not in controls. The current work studies the cooperation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…We evaluated whether MAPKs were able to induce expression of ODC, the first and rate‐limiting enzyme in polyamine biosynthesis 18, 19. We found that CAP (2 μmol/L) was able to induce a significant increase in protein expression of ODC; however, in the presence of KN‐93 or the p38‐selective inhibitor BIRB‐796, the expression of ODC was greatly downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated whether MAPKs were able to induce expression of ODC, the first and rate‐limiting enzyme in polyamine biosynthesis 18, 19. We found that CAP (2 μmol/L) was able to induce a significant increase in protein expression of ODC; however, in the presence of KN‐93 or the p38‐selective inhibitor BIRB‐796, the expression of ODC was greatly downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of polyamine uptake potentiates the anti-proliferative effect of polyamine synthesis inhibition and preserves [17]. Overexpression of ODC was found to decrease ventricular systolic function during cardiac hypertrophy through assessment of the left ventricular ejection fraction (LVEF) and shortening fraction (FS) by echocardiography [18]. Cardiac fibrosis was identified using Masson staining and TUNEL was also used to detect the apoptosis of the myocardium from ISO-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The control group received saline only. L-Arginine was dissolved in drinking water (5%, w/v), [17][18][19] corresponding to a dose of about 330 mg per day per animal, and pH was adjusted to 7. L-Arginine supplementation was started 3 days before the surgical procedure and administered until the end of the experiment.…”
Section: Animals and Treatmentsmentioning
confidence: 99%